The Association between Mean Platelet Volume and Albuminuria in Patients with Type 2 Diabetes Mellitus at King Abdul-Aziz Medical City, Jeddah 2020 - Alzahrani, Abdullah M; Alesa, Alaa A; Yaghmour, Aisha E; Khan, Muhammad Anwar; Alesa, Abdullah A (Archives of Clinical and Biomedical Research, 2021)
Background: Diabetic patients are at greater risk for many complications. They also are considered to be in hypercoagulable state. Larger platelets are associated with a prothrombotic states because larger platelets are more active. Patients with type 2 diabetes mellitus are usually found to have an elevated MPV. Albuminuria is a very important predictor for both cardiovascular complications and diabetic nephropathy. We aimed in this study to find the association between MPV in diabetic patients and microalbuminuria, HbA1c level, duration of DM, body mass index (BMI), hypertension, stroke, and ischemic heart disease. Methods: A cross sectional quantitative study of diabetic patients. The data was collected retrospectively from the patients’ electronic files. It included 480 diabetic patients from June 2016 until December 2020. Sample size consisted of 480 patients and it included both male and female patients who are 18 years or older. The data that was collected included gender, duration of DM, HTN, IHD, history of stroke, MPV, albuminuria, BMI and HbA1c. Results: There was no statistically significant association between MPV and most of the designated variables including Gender, IHD, Stroke, HTN and Albuminuria. Furthermore, there was no association between MPV and albuminuria according to blood sugar level. It was also found that the higher the albuminuria the higher the MPV; the mean MPV increases in patients with increased albuminuria. Conclusions: MPV and albuminuria were positively correlated. MPV was higher in the controlled diabetes group. However, the association was not statistically significant.